MENINGKATKAN KESADARAN MASYARAKAT DESA TONGO MELALUI EDUKASI BULLYING - Sintia Ismail; Sri Saidawati Mahmud; Adnan Malaha; Moh. Wahid (STKIP Subang, 2025)
This research aims to increase the awareness of the Tongo Village community, Bonepantai District, Bone Bolango Regency, regarding the phenomenon of bullying through educational programs. The background of this study lies in the community’s low understanding of bullying, which is often perceived as mere joking or normal interaction. This study applied a qualitative approach with a descriptive method through interviews, observations, and documentation. The findings reveal that family, economic conditions, social environment, and peer interaction are the main factors contributing to bullying in Tongo Village. After implementing educational activities through village socialization, school programs, the involvement of community leaders, and youth participation, there was a noticeable improvement in understanding and behavioral change among residents. The community began to show courage in correcting and reporting bullying cases while also developing empathy toward victims. Thus, education proved effective in fostering collective awareness and creating a more harmonious social environment free from bullying.